Integration of Oral Literature in Teaching and Learning Literature in Selected Secondary Schools in Ntungamo District. - Ahimbisibwe, Monicah (Kabale University, 2024)
The study focused on the integration of oral literature into the teaching and learning of literature in selected secondary schools in the Ntungamo District. Its objectives were to examine the extent to which oral literature is integrated into literature teaching, propose ways to incorporate oral literature into the curriculum while preserving its performative characteristics and evaluate the impact of oral literature on learners in society. The study employed a survey design, collecting data through questionnaires and interviews to capture information about individuals' attitudes, opinions, and practices. Findings revealed that a majority of respondents (70.8%) reported implementing specific strategies to maintain the performative elements of oral literature, reflecting an understanding of the importance of preserving traditional oral narratives in the classroom. The study concluded that although oral literature is valued in education, its integration into the secondary school curriculum in Nthe tungamo District is inconsistent. Effective integration requires a supportive educational framework, including sufficient resources, specialized teacher training, and curriculum modifications to incorporate the performative aspects of oral literature fully. The study recommended specialized training for literature teachers to equip them with skills to teach oral literature effectively using creative and interactive methods. Additionally, it suggested providing schools with resources such as recordings of oral literature, detailed lesson plans, and teaching aids to facilitate its integration into the curriculum.